Anti-inflammaging and antiglycation activity of a novel botanical ingredient from African biodiversity (Centevita™) - Maramaldi G; Togni S; Franceschi F; Lati E (Dove Medical Press, 2013)
Giada Maramaldi,1 Stefano Togni,1 Federico Franceschi,1 Elian Lati21Indena SpA, Milan, Italy; 2Laboratoire BIO-EC, Longjumeau, FrancePurpose: The aim of this study was to investigate the topical efficacy of a new purified extract from Madagascar, Gotu Kola (Centella asiatica [L.] Urban), both on human explants and on human volunteers, in relation to skin wrinkling and skin protection against ultraviolet light exposure. The extract, with a peculiar content of biologically active molecules, was investigated as a novel anti-inflammaging and antiglycation agent. Its typical terpenes, known as collagen synthesis promoters, represent at least 45% of the extract. It also contains a polyphenolic fraction cooperating to the observed properties.Methods: C. asiatica purified extract was assayed on human skin explants maintained alive, and several parameters were evaluated. Among the most relevant, the thymine dimerization was evaluated by immunostaining. Malondialdehyde formation was evaluated as free-radical scavenging marker by enzyme-linked immunosorbent assay. The expression of interleukin-1a was observed by enzyme-linked immunosorbent assay as well. The product was further evaluated as an antiglycation agent, being glycation quantified by the advanced glycation product carboxymethyl lysine. C. asiatica purified extract was also evaluated as an antiwrinkling agent in a single-blind, placebo-controlled study. Formulated in a simple oil-in-water emulsion, the extent of wrinkling was assessed by skin replicas, skin firmness, skin elasticity, and collagen density measurements.Results: C. asiatica purified extract could protect DNA from ultraviolet light-induced damage, decreasing the thymine photodimerization by over 28% (P<0.05). A reduced (26%, P<0.01) expression of interleukin-1α was also observed, supporting its anti-inflammatory potential. C. asiatica purified extract showed in vitro a total inhibition of carboxymethyl lysine formation induced by the glycating agent methylglyoxal. A clear epidermal densification of collagen network in the papillary dermis was observed. These in vitro data have been confirmed by clinical results.Conclusion: These results qualify C. asiatica purified extract as an antiaging ingredient, addressing skin damage caused by inflammaging and glycation by relying on the synergy of triterpens and polyphenolics.Keywords: Centella asiatic, glycation, inflammaging, skin aging, collagen, triterpenes